Implementation of Islamic Religious Education Curriculum Based on Religious Moderation - Faiqatul munawwarah; Heni Listiana (Classroom: Journal of Islamic Education, 2025)
The issues today are still related to radicalism that results in terrorism and bulliying as well as other forms of oppression. Religious moderation is needed in the world of education so that integration with the Islamic Religious Education curriculum is important. The purpose of this study is to explain the application of the Islamic Education curriculum based on religious moderation. The research method uses a qualitative approach qualitative approach of literature review method. Data sources are taken from several scientific literature related to the research title and then analysed. The result of the research shows that religious moderation in Islamic Religious Education plays an important role in shaping the character of students who are balanced, tolerant, and tolerant. in shaping the character of students who are balanced, tolerant, and inclusive, by teaching the values of balance, tolerance, justice, and inclusiveness. inclusive, by teaching the values of balance, tolerance, justice, and peace to create harmony in the middle of the world. peace to create harmony in the midst of diversity.  Steps for implementing religious moderation in the Islamic Religious Education curriculum, a) inserting the values of moderation in the Islamic Religious Education material. in Islamic Religious Education materials. b) optimising learning approaches that develop tolerance, critical thinking, and inclusiveness. c) organising special programmes or training. d) implementing religious moderation in the Islamic Religious Education curriculum. organising special programmes or training. d) conducting evaluations. To prevent radicalism, religious moderation moderation needs to be applied by emphasising balance, tolerance and dialogue. dialogue. The conclusion is that religious moderation can prevent forms of oppression and damage caused by applying the principles of moderation. and the damage caused by applying the principle of moderation.